Milestones in acute GVHD pathophysiology - Socie, Gerard; Michonneau, David (Frontiers in Immunology, 2022)
In the past 65 years, over 25 000 referenced articles have been published on graft-versus-host disease (GVHD). Although this included clinically orientated papers or publications on chronic GVHD, the conservative estimate of scientific publications still contains several thousands of documents on the pathophysiology of acute GVHD. Thus, summarizing what we believe are prominent publications that can be considered milestones in our knowledge of this disease is a challenging and inherently biased task. Here we review from a historical perspective what can be regarded as publications that have made the field move forward. We also included several references of reviews on aspects we could not cover in detail.